2004
DOI: 10.1124/jpet.104.065557
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Disposition and Effects of Nitric Oxide Donors: Rapid and Concentration-Dependent Reduction in the Cytochrome P450-Mediated Drug Metabolism in Isolated Perfused Rat Livers

Abstract: Various mechanisms, including high levels of cytokines and nitric oxide (NO), have been proposed as mediators for inflammation-induced cytochrome 450 down-regulation. However, the contribution of each of these mediators to the observed effects is controversial. We used an isolated perfused rat liver (IPRL) model to test the direct effects of NO donors on CYP450 down-regulation in the absence of cytokines or other confounding in vivo factors. Our hypothesis was that NO rapidly and concentration-dependently decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…NO can bind to P450s and cause inhibition by reversible or irreversible pathways [14,15], and therefore NO may be one cause of the enzyme inhibition observed in inflammatory states [16,17]. Stimulation of NO synthesis may also be involved in the down-regulation of hepatic CYP mRNAs or proteins by inflammation, because these effects could be blocked or attenuated by NOS inhibitors in either in vivo or cell culture models [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…NO can bind to P450s and cause inhibition by reversible or irreversible pathways [14,15], and therefore NO may be one cause of the enzyme inhibition observed in inflammatory states [16,17]. Stimulation of NO synthesis may also be involved in the down-regulation of hepatic CYP mRNAs or proteins by inflammation, because these effects could be blocked or attenuated by NOS inhibitors in either in vivo or cell culture models [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The role of cytokines in this down-regulation is relatively well established; they are known to inhibit drug metabolism by acting at the level of gene transcription (Ghezzi et al, 1986;Warren et al, 1999). However, the role of NO is still subject to controversy (Sewer and Morgan, 1998), although it has been proposed that NO acts at both transcriptional and post-translational levels (Khatsenko et al, 1993;Wink et al, 1993;Minamiyama et al, 1997).Very recently, we reported that the effects of NO on P450 are rapid, concentration-dependent, and enzyme-selective (Vuppugalla and Mehvar, 2004a). Additionally, we also showed that the effects of NO are time-dependent, consisting of both reversible and irreversible components (Vuppugalla and Mehvar, 2004b).…”
mentioning
confidence: 68%
“…Very recently, we reported that the effects of NO on P450 are rapid, concentration-dependent, and enzyme-selective (Vuppugalla and Mehvar, 2004a). Additionally, we also showed that the effects of NO are time-dependent, consisting of both reversible and irreversible components (Vuppugalla and Mehvar, 2004b).…”
mentioning
confidence: 80%
See 2 more Smart Citations